Pyrolysis behaviors and kinetics of refining and chemicals wastewater, lignite and their blends through TGA. (March 2015) - Mu, Lin; Chen, Jianbiao; Yin, Hongchao; Song, Xigeng; Li, Aimin; Chi, Xiao
Highlights: Wastewater was mixed with lignite and the co-pyrolysis behaviors were studied. The pyrolysis of RS and blends proceeded in three stages, but two stages for HL. There existed inhibitive interactions between RS and HL. The activation energies were calculated by using the Friedman and Starink method. The minimum average activation energy was obtained by blending 75% RS. Abstract: Co-pyrolysis behaviors of refining and chemicals wastewater solid (RS) and Huolinhe lignite (HL) were investigated via thermogravimetric analysis (TGA). The thermal degradation process of RS and the blends proceeded in three stages, while two stages for HL. The increased percentage of RS in the blends reduced the characteristic temperature ( T i, T p, T f ) and residual mass ( M r ), while raised the characteristic reaction rate ( R p, R v ) and comprehensive devolatilization parameter ( D ). The results indicated that there existed some inhibitive interactions between RS and HL. The activation energies were calculated by using the Friedman and Starink method. The activation energy of RS increased first and then decreased with conversion degree, and the variation wasn't as great as that of the blends and lignite. No matter which conversion degree is, the activation energy decreased with the percentage of RS in the blends increasing. The minimum value was obtained by blending 75 wt.% RS.